Analysing the Economic and Environmental Impact of Electric Vehicle Diffusion on the Malaysian Economy - Johari, Ismaily; Mohamed Yusoff, Nora Yusma (International Journal of Energy Economics and Policy, 2026)
The transition to electric vehicles (EVs) is increasingly viewed as a key strategy in decarbonising the transport sector, with far-reaching implications for national economies and energy systems. This study evaluates the macroeconomic, employment and environmental impacts of large-scale EV adoption in Malaysia using an environmentally extended input-output (EEIO) model. Two scenarios are evaluated for the different EV share targets (30%, 50% and 80%): (i) a shift in demand from petroleum to electricity due to EV use, and (ii) a structural transformation of the vehicle manufacturing sector from internal combustion engine (ICE) to EV. The results reveal modest benefits from fuel substitution alone, but larger gains from transitioning to EV manufacturing. However, the environmental gains remain limited without decarbonising the electricity mix. The study highlights critical trade-offs and emphasises the need for coordinated policy strategies linking transport electrification with clean energy deployment, labour market transition support, and green industrial development. These findings offer evidence-based guidance for managing Malaysia’s low-carbon mobility transition in line with economic and climate policy objectives.